تصميم هوائي مطبوع متعدد المقاييس للتطبيقات متعددة الحزم الترددية - صالح, السموءل (Latakia University Journal -Engineering Sciences Series, 2016)
The technical development in telecommunication creates multi-applications devices. These devices work on various frequencies or multi-band frequencies for applications like wireless internet, Boletus, wifi, etc. . These applications require a new type of antenna that works on large band frequencies or multi-band. Some proposed antennas are the dipole array antenna, fractal antenna and multi-scales antenna or multi-dimensions antenna. This paper suggests new multi-scale antennas design with large band frequencies. This antenna depends on a micro-stripe patch antennas with multi-dimensions resonance patches or apertures, that correspond to an intended application. The Zland simulator will be applied for studying the suggested antenna and analyzing the effect of the variation of resonance patch numbers and dimensions on the antenna proprieties. سمح التطور التقني في مجال الاتصالات بوجود عدد من الأجهزة التي تقوم بمهام مختلفة أي تعمل على حزم ترددية مختلفة، أو تغطي مجالا تردديا عريضا، وذلك من اجل تطبيقات متعددة مثل الانترنت اللاسلكية، البلوتوث، الـ Wifi و.... تطلب ذلك تطوير هوائيات متعددة الحزم الترددية أي ذات طيف استقبال عريض، عن طريق استخدام هوائيات الدايبول المصفوفية، الهوائيات التجزيئية، الهوائيات متعددة المقاييس أي الهوائيات مختلفة الأبعاد أو مختلفة الفتحات الطنينية. هذا العمل يقدم اقتراحا جديدا لتصميم هوائي مطبوع عريض الحزمة أو متعدد الحزم الترددية وذلك اعتمادا على تصميم هوائي رقعي بفتحات رنينيه متعددة الأبعاد، تعمل عند عدة ترددات رنين توافق التطبيق المراد استخدامه. سيتم تطبيق برنامج Zland, لدراسة خصائص الهوائي المقترح ودراسة التغيرات الحاصلة على معاملات الهوائي تبعا لتغيرات عدد وأبعاد الفتحات الرنينية المقترحة على الهوائي بشكل عام.